Application of Waterfall Method on Employee Payroll Management System with Codeigniter Framework - Wahyudi, Heri; Rian Putra, Supiyandi; Yusman, Yanti (Cattleya Darmaya Fortuna, 2024)
Salary is a form of periodic payment from an employer to an employee that is stated in an employment contract. From a business execution point of view, salaries can be considered as the cost needed to get human resources to work. The payroll management system was built to make it easier to view digital payslips, so that deductions charged in payroll can be known. The results of the study built a payroll management system for honorary employees of the Office of the Ministry of Informatics of North Sumatra by applying the waterfall method, by applying the waterfall method to produce effective applications because it has gone through the testing process, besides that in building a payroll management system to make it more attractive using the codeigniter framework